Pre-treatment and post-treatment nasopharyngeal carcinoma imaging: imaging updates, pearls and pitfalls. - Li, Kwok Yan; Kwok, Hoi Ming; Pan, Nin Yuan; Cheng, Lik Fai; Ma, Ka Fai Johnny (Neuroradiology, 2025)
Purpose: Nasopharyngeal carcinoma (NPC) is endemic in Southeast Asia, requiring precise imaging for personalized treatment. This review highlights key imaging challenges and updates from recent literature, emphasizing findings that impact oncological management. Methods: We discuss common and uncommon clinical entities, detailing salient imaging features and diagnostic distinctions to aid accurate interpretation. Results: In the pre-treatment setting, leveraging the characteristic MR signals and spread patterns of NPC aids in defining the tumor volume for accurate staging and radiotherapy contouring. Key diagnostic challenges include differentiating tumor from benign hyperplasia, skull base osteomyelitis, and other skull base tumors. Perineural tumor spread, radiological extranodal extension and nodal necrosis further refine primary tumor and nodal assessment. In the post-treatment setting, the key question is whether tumor recurrence exists. Diagnostic challenges involve distinguishing tumor recurrence from scar tissue, post-radiation nasopharyngeal necrosis, or hypertrophied cervical ganglia. For recurrences, endoscopic nasopharyngectomy has emerged as the preferred approach over open surgery or re-irradiation. The text highlights characteristic post-treatment appearances and emphasizes recognizing these patterns to avoid misinterpretation and guide appropriate management. Conclusion: Imaging plays a pivotal role in NPC precision oncology. Mastering imaging pearls and pitfalls empowers radiologists to provide clinicians with reliable, actionable guidance.